First person - Cathryn Ugalde (The Company of Biologists, 2020)
First Person is a series of interviews with the first authors of a selection of papers published in Disease Models & Mechanisms, helping early-career researchers promote themselves alongside their papers. Cathryn Ugalde is first author on 'Misfolded α-synuclein causes hyperactive respiration without functional deficit in live neuroblastoma cells', published in DMM. Cathryn is a postdoctoral research scientist in the lab of Prof. Andrew Hill at La Trobe University, Bundoora, Australia, investigating neurodegeneration associated with protein misfolding.